El Excentrico, 1958-07-20 - Garcia, Humberto:::Publisher:::::::::::: (Garcia Printing; San Jose, California, 2023)
July 20, 1958 [20 de julio de 1958]. Ano 8, No. 22. Cover contains a photo of Del Socorro Ramierez, in formal wear, holding flowers and a trophy. She has won the 1958 C.S.O Beauty Contest. The headline reads, "Miss Ma. Del Socorro Ramirez- Winner C.S.O. Beauty Contest."